Plant-soil interactions and C:N:P stoichiometric homeostasis of plant organs in riparian plantation - Ding, Dongdong; Arif, Muhammad; Liu, Minghui; Li, Jiajia; Hu, Xin; Geng, Qianwen; Yin, Fan; Li, Changxiao (Frontiers in Plant Science, 2022)
Carbon (C), nitrogen (N), and phosphorus (P) stoichiometric ratios give valuable insight into ecosystem function. The purpose of the present study is to probe into the C, N, and P stoichiometric characteristics in various organs and their relationships with soil factors of the dominant deciduous conifer plant species (Taxodium ascendens and Taxodium distichum) during afforestation in the riparian zone of Three Gorges Reservoir. The results showed only a small change in the concentration of C in different plant organs and soils. T. ascendens contained mean N and P concentrations of 7.63 and 1.54 g/kg in fine roots, 5.10 and 0.56 g/kg in stems, and 15.48 and 2.30 g/kg in leaves, respectively. Whereas T. distichum had a mean N and P concentration of 7.08 and 1.37 g/kg in fine roots, 4.84 and 0.59 g/kg in stems, and 16.89 and 2.23 g/kg in leaves. The N:P ratios in all organs were below 14, indicating that N may have inhibited tree growth. The fine roots P and N:P of T. distichum were weak plasticity and weak homeostasis, and those of T. ascendens were plasticity and weak plasticity. Their stems and leaves adhere to strict homeostasis. N concentrations were significantly positively related to P concentrations in every tissue (except the stems of T. ascendens), and C concentrations were significantly positively associated with P concentrations in the stems and leaves of T. ascendens and T. distichum (p < 0.05). Likewise, soil P and fine root P were positively associated (p < 0.01). This study contributes to the understanding of deciduous conifer plant stoichiometry. It demonstrates N, P, and N:P stoichiometric homeostasis in T. ascendens and T. distichum, which can withstand flooding and are suitable for vegetation restoration in the hydro-fluctuation zone.